Relativistic Electron and Proton Experiment for the HENON mission: simulated performance - Ngom, Catherine; Oleynik, Philipp; Virtanen, Pasi; Raukunen, Osku; Peltonen, Juhani; Peltola, Tatu; Säntti, Tero; Punkkinen, Risto; Punkkinen, Arttu; Anantha Raman, Deepa; Lehti, Jussi; Marcucci, Maria Federica; et al. (EDP Sciences, 2026)
HEliospheric pioNeer for sOlar and interplanetary threats defeNce (HENON) is a 12U CubeSat that will explore for the first time ever the Distant Retrograde Orbit in the Sun-Earth system, bringing a payload suited for Space Weather observations and science. Initially designed for the Foresail-2 nanosatellite mission, the Relativistic Electron and Proton Experiment (REPE) instrument has since evolved for deployment in a variety of future missions, including the HENON mission. REPE is a particle telescope developed to measure fluxes of high-energy electrons and protons over broad ranges of energies, relevant to the space radiation environment. The instrument is designed to measure electron energy spectrum from 0.1 to 10.4 MeV and proton energy spectrum from 2 to hundreds of MeV. We present Monte Carlo simulations of REPE performance using Geant4. We evaluate the performance in terms of sensitivity (geometric factor), energy resolution, and cross-contamination between measured species. We show that the instrument meets the scientific requirements of the mission.